2017
DOI: 10.2460/javma.251.9.1053
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of laparoscopic ovariohysterectomy or ovariectomy in dogs with von Willebrand disease or factor VII deficiency: 20 cases (2012–2014)

Abstract: OBJECTIVE To describe surgical techniques and perioperative management of dogs with von Willebrand disease (VWD) or factor VII (FVII) deficiency undergoing laparoscopic ovariohysterectomy or ovariectomy and evaluate outcomes. DESIGN Retrospective case series. ANIMALS 20 client-owned dogs with VWD (n = 16) or FVII deficiency (4). PROCEDURES Dogs with VWD or FVII deficiency that underwent laparoscopic ovariohysterectomy or ovariectomy between 2012 and 2014 were retrospectively identified via a multi-institutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Classification of studies by organ system is presented in Tables S1 and S2. Numbers of studies and participants were reported within each organ/system group including female genital tract (22 studies [n = 1407 dogs]), 1,7,11,20,30‐47 urinary tract (7 studies [n = 114]), 3,48‐53 stomach (9 studies [n = 250]), 10,18,54‐59 intestinal tract (5 studies [n = 48]), 60‐64 liver (5 studies [n = 288]), 12,17,65‐67 adrenal gland (5 studies [n = 62]), 13,28,68‐70 spleen (7 studies [n = 111]), 19,71‐76 and other (4 studies that included gastropexy and ovariectomy procedures [n = 148]) 9,77‐79 . One experimental study, in which colopexy in seven male dogs was described, was classified as intestinal tract even though these dogs were also sterilized during the surgical procedure because this study reported only complications and outcomes related to colopexy 63 .…”
Section: Resultsmentioning
confidence: 99%
“…Classification of studies by organ system is presented in Tables S1 and S2. Numbers of studies and participants were reported within each organ/system group including female genital tract (22 studies [n = 1407 dogs]), 1,7,11,20,30‐47 urinary tract (7 studies [n = 114]), 3,48‐53 stomach (9 studies [n = 250]), 10,18,54‐59 intestinal tract (5 studies [n = 48]), 60‐64 liver (5 studies [n = 288]), 12,17,65‐67 adrenal gland (5 studies [n = 62]), 13,28,68‐70 spleen (7 studies [n = 111]), 19,71‐76 and other (4 studies that included gastropexy and ovariectomy procedures [n = 148]) 9,77‐79 . One experimental study, in which colopexy in seven male dogs was described, was classified as intestinal tract even though these dogs were also sterilized during the surgical procedure because this study reported only complications and outcomes related to colopexy 63 .…”
Section: Resultsmentioning
confidence: 99%
“…Improving healthcare for the future An example of a genetic condition, where knowing about the condition early in the animal's life could allow for better healthcare provision, is von Willebrand disease. This is the most common inherited coagulopathy in dogs -estimated to affect 1.5% of the population (Keeshen et al, 2017). It is particularly associated with the Doberman Pinscher, although it has been identified in 54 breeds (Crespi et al, 2018).…”
Section: Nationwide Dna Profilingmentioning
confidence: 99%